감자 24품종의 농업적 형질의 유전형과 재배환경의 상호작용 효과 - 김수정(Su Jeong Kim); 손황배(Whang Bae Sohn); 박민우(Min Woo Park); 장동칠(Dong Chil Chang); 홍수영(Su Young Hong); 권오근(Oh Keun Kwon); 정진철(Jin Cheol Cheong); 구본철(Bon Cheol Koo); 김율호(Yul Ho Kim) (Korean journal of breeding, 2018)
The 24 potato cultivars grown in three regions with different cultivation environments were investigated genotype and environment interaction (GEI) using the Additive Main Effects and Multiplicative Interaction (AMMI), and Genotype main effect and genotype by environment interaction (GGE) biplot model analysis. Potato yield was highly related to environment and GEI factors but the number of tubers and dry matter content were related to the genotype factor. Potato yield was the highest in 'Seohong' in Gangneung, 'Dejima' in Jinbu area, and 'Saebong' in Daegwallyeong area. As a result of analysis of GEI effect between genotypes and environment, 'Seohong' in yield, 'Daejima in tuber, and 'Goun' in dry matter content were superior and were stable. The ‘Seohong’, which has the highest yield and stability, showed promising results and can substitute the ‘Superior’ variety. The 'Goun' was selected as a chip potato processing grade to replace 'Dejima', which currently is the major processing grade. Therefore, as a result of analysis of AMMI and GGE biplot models of agricultural traits of potatoes showed that the cultivation environment has greatest influence on the yield. Therefore, proper site selection for the desired cultivar is necessary for best results. Though it is also important to select the best genotype with a high dry matter content. KCI Citation Count: 0